RAPD markers reveal genetic variation between Cichorium spinosum L. and Taraxacum sp.; a substantial medicinal plants of Greece - Shidfar, Mina; Keskin, Sıddık; M. Khah, Ebrahim; Petropoulos, Spyridon; Ozdemir, Fethi Ahmet; Gokcen, Ibrahim Samet (Progress in Nutrition, 2018)
Fifteen Random Amplified Polymorphic DNA (RAPD) markers were used to measure genetic diversity and genetic relationships between five endemic genera of Mediterranean basin (Greece). Three species of Cichorium spinosum were collected; two from island Crete (Greece) and one from island Kythnos, and other two species of Taraxacom sp. (Asteraceae); are from Orhomenos and Athens. Two hundred-forty amplified products and 163 RAPD bands were scored with an average of 67.91% of them revealing polymorphism across accessions. In this research OPD-05 primer with 24 bands showed the highest number of bands, while the OPM-18 and OPB-16, both of them with 8 bands showed the least number of bands. Also OPV-06 primer with 18 polimorphic bands showed the highest number of bands. The least number of polymorphic bandswere found in OPX-18. UBC-292, OPAN-01, OPB-16, OPM-18, OPD-05 primers. Subsequently, OPD-05 primer with 29.16% showed the least percentage of polymorphism degree, whereas OPM-18 and OPB-16 primers with 87.50% showed the highest percentage of polymorphism. UPGMA clustering based on data from polymorphic RAPD bands revealed two distinct group which joined to form one major cluster at 32% level of similarity. Also Cichorium spinosum, Crete and Cichorium spinosum, Kythnos, varieties with 100% similarity are synonyms. The similarity indices of the RAPD dendrogram ranged between 30% and 100% averagely high enough to suggest useful variability for genetic diversity and plant breeding.